2008
DOI: 10.1007/s12192-008-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of gnotobiotic Artemia franciscana larvae to abiotic stress promotes heat shock protein 70 synthesis and enhances resistance to pathogenic Vibrio campbellii

Abstract: Larvae of the brine shrimp Artemia franciscana serve as important feed in fish and shellfish larviculture; however, they are subject to bacterial diseases that devastate entire populations and consequently hinder their use in aquaculture. Exposure to abiotic stress was shown previously to shield Artemia larvae against infection by pathogenic Vibrio, with the results suggesting a mechanistic role for heat shock protein 70. In the current report, combined hypothermic/hyperthermic shock followed by recovery at am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 55 publications
1
69
0
Order By: Relevance
“…HSP70 has the ability to protect cells from the deleterious effects of inflammation; for example, by refolding and stabilizing denatured protein aggregates. 31 In this study, we found that inflammatory cytokines (TNF-a and IL-1b) and HSP70 synthesis were significantly increased in chronic bacterial prostatitis. This finding is similar to earlier studies of other inflammation diseases, which showed that levels of the inflammatory cytokine IL-1b and HSP70 are both increased in rats infected with E. coli.…”
Section: Discussionmentioning
confidence: 55%
“…HSP70 has the ability to protect cells from the deleterious effects of inflammation; for example, by refolding and stabilizing denatured protein aggregates. 31 In this study, we found that inflammatory cytokines (TNF-a and IL-1b) and HSP70 synthesis were significantly increased in chronic bacterial prostatitis. This finding is similar to earlier studies of other inflammation diseases, which showed that levels of the inflammatory cytokine IL-1b and HSP70 are both increased in rats infected with E. coli.…”
Section: Discussionmentioning
confidence: 55%
“…Feeding with bacteria, apart from virulent strains such as V. campbellii (Soltanian et al 2007;Sung et al 2008), V. proteolyticus (Marques et al 2006a;Sung et al 2007), and V. harveyi (Soto-Rodriguez et al 2003;Defoirdt et al 2006), enhances Artemia resistance against disease and infection. As one example, colonization of cultures with nine different live bacterial strains protected Artemia juveniles against V. proteolyticus CW8T2 (Verschuere et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio challenge of Artemia larvae Axenic Artemia larvae were obtained by cyst decapsulation (Sorgeloos et al 1986) followed by incubation at 28°C for 24 h in sea water (Sung et al 2008). Larvae developing within the next 4-6 h, and thus with the ability to ingest bacteria, were harvested and incubated for 6 h with either heat-shocked or nonstressed bacteria at approximately 1× 10 7 cells per milliliter.…”
Section: Inductionmentioning
confidence: 99%
See 2 more Smart Citations